Introduction to bond graphs and their applications - Thoma, Jean U. (Jean Ulrich), 1927- (Pergamon international library of Science, technology, engineering and social studies, 1975)
Introduction to Bond Graphs and Their Applications is an introductory text on bond graphs and their applications in the field of engineering. The applications of bond graphs in mechanical engineering and design, fluid mechanics, electronic data processing, and thermal and thermodynamic systems are discussed. This book is comprised of eight chapters and begins by comparing the different kinds of graphs, diagrams, and models before turning to the fundamentals of bond graphs. The next chapter introduces the reader to the systematic application of bond graphs in mechanical engineering and design.